2009
DOI: 10.1007/s00198-009-1031-x
|View full text |Cite
|
Sign up to set email alerts
|

PTH improves titanium implant fixation more than pamidronate or renutrition in osteopenic rats chronically fed a low protein diet

Abstract: Summary We evaluated the effects of parathyroid hormone (PTH), pamidronate, or renutrition on osseointegration of titanium implants in the proximal tibia of rats subject to prolonged low-protein diets. PTH improved mechanical fixation, microarchitecture, and increased pull-out strength. Pamidronate or renutrition had lesser effects. PTH can thus improve implant osseointegration in protein-malnourished rats. Introduction Protein malnutrition impairs implant osseointegration in rats. PTH and pamidronate prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…On the other hand, teriparatide may be advantageous for efficient osteointegration due to its ability to activate osteoblasts. Indeed, previous animal experimental studies showed the superiority of teriparatide over bisphosphonate in the mechanical fixation of the implant [26] and in the bone volume around the implant [27]. Also, this study revealed that teriparatide treatment caused high levels of the bone-formation marker (P1NP) to be maintained for 1 year after surgery, which may contribute to the efficient biological fixation of the implant.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, teriparatide may be advantageous for efficient osteointegration due to its ability to activate osteoblasts. Indeed, previous animal experimental studies showed the superiority of teriparatide over bisphosphonate in the mechanical fixation of the implant [26] and in the bone volume around the implant [27]. Also, this study revealed that teriparatide treatment caused high levels of the bone-formation marker (P1NP) to be maintained for 1 year after surgery, which may contribute to the efficient biological fixation of the implant.…”
Section: Discussionmentioning
confidence: 53%
“…Mechanical loading on the bone in vivo influences positively the bone mass, promotes the increase of its density and strength, which is confirmed by the data of studying microarchitectures of the lamellar and trabecular bone [4,5,7].…”
supporting
confidence: 54%
“…In particular, such disease as osteoporosis or insufficient dietary intake of protein can negatively affect the quality of the compact bone tissue and impair the process of implant osseointegration as well [3]. And conversely, systemic treatment of osteoporosis can improve osseointegration influencing positively the architectonics and composition of the bone tissue being formed around implants contributing to a greater mechanical strength of the forming bone-implant block [4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include the bone morphogenetic proteins (BMPs), in particular BMP-2 and BMP-7 or osteogenic protein-1 (OP-1), and growth factors such as platelet-derived growth factor (PDGF), insulin-like growth factor (IGF), and transforming growth factor-beta 1 (TGF‚-1) alone or combined with IGF-1, and TGF (Mavrogenis et al, 2009). Other biological coatings that have been used to improve osseointegration of titanium implants include collagen and other extracellular matrix proteins such as fibronectin and vitronectin (Ku et al, 2005), and systemic administration of pharmacological agents such as ibandronate and human parathyroid hormone (Dayer et al, 2010).…”
Section: Incorporation Of Biologically Active Drugs Into Titanium Denmentioning
confidence: 99%